Pemodelan 2D sistem pana bumi daerah Garut Bagian Timur menggunakan metode magnetotelurik - Riznia Aji Salam; Udi Harmoko; Tony Yulianto (Youngster Physics Journal, 2017)
This research was conducted in the eastern part of the Garut area using magnetotelluric method that aims to create 2D model of the geothermal system based on distribution of rock resistivity value. Magnetotelluric method is used because it is able to identify subsurface structure to a depth of thousands of meters. In this research, the data measured from 9 different targets area and processed based on the flow such as converting time domain data into the frequency domain, identify noise data, perform two-dimensional inversion modeling and create geothermal systems. Based on the results, also compared with the interpretation of geological data and geochemistry of rocks known clay cap, reservoir, and hot rock. Furthermore, Clay cap has a value of 4-32 Ωm resistivity on depth of 3000 m. Reservoir rock with resistivity value of 64-512 Ωm at a depth of 1500-5000 m. While hot rock with 1024-8192 Ωm resistivity value is under the reservoir rock.Keywords: Magnetotelluric, Eastern section of the Garut, geothermal system, resistivity